Kebutaan Akibat Kelainan di Fundus - A. Soemarsono, A. Soemarsono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1985)
The mechanism of blindness by fundus anomalia was presented. The criteria of blindness were determined by visual acuity 3/60 or less. During a one-year period from januafy to December 1983 there were found 71 cases of blindness of both eyes and-78 cases of blindness of one eye. The kinds of blindness found at Dr. Sardjito Hospital were retinitis/choziorecinitis 27 patients, retinopathy 17 patients, glaucoma 69 patients, N 11 atrophy 16 patients, macula degeneration 2 patients, and retinal bleeding 2 patients, All the blindness were irreversible. Key Words: blindness - fundus anomalia - chorioretinitis retinopathy glaucoma